2006
DOI: 10.1118/1.2357835
|View full text |Cite
|
Sign up to set email alerts
|

Improving IMRT dose accuracy via deliverable Monte Carlo optimization for the treatment of head and neck cancer patients

Abstract: The purpose of this work is to investigate the effect of dose-calculation accuracy on head and neck (H&N) intensity modulated radiation therapy (IMRT) plans by determining the systematic dose-prediction and optimization-convergence errors (DPEs and OCEs), using a superposition/convolution (SC) algorithm. Ten patients with locally advanced H&N squamous cell carcinoma who were treated with simultaneous integrated boost IMRT were selected for this study. The targets consisted of gross target volume (GTV), clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 36 publications
0
52
0
Order By: Relevance
“…Several studies showed the impact of highly accurate MC dose calculations for lung and IMRT treatments [1,6,7,34]. However in most of these studies, MC dose calculation was performed with research tools and taken as a benchmark for the clinical dose computations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed the impact of highly accurate MC dose calculations for lung and IMRT treatments [1,6,7,34]. However in most of these studies, MC dose calculation was performed with research tools and taken as a benchmark for the clinical dose computations.…”
Section: Discussionmentioning
confidence: 99%
“…From obtained dose values, the percentage dose prediction error (%DPE) was calculated [7,26]. Assuming that the MC algorithm is more accurate, %DPE ecc was defined as (3) where x is the given dose-volume index (maximum, minimum, or mean dose).…”
Section: Dvh Analysismentioning
confidence: 99%
“…One of the studies ( 14 ) utilized two‐stage optimization process, where fluence maps optimization and their conversion into multileaf collimator (MLC) trajectories are separated. The other work utilized deliverable ( 15 18 ) optimization, where the fluence‐map‐to MLC trajectories conversion is incorporated into the optimization process, thereby explicitly accounting for MLC leaf position weights.…”
Section: Introductionmentioning
confidence: 99%
“…In the clinic, g should be applicable to nearly any application requiring high dose accuracy, such as beam modeling, 21 IMRT optimization, 42 dosimeter response modeling, 28,43 dose validation, 19 dose accumulation, 44 among others. As an example, due to the three-source nature of the MRIdian system, quasi-3D dosimeters, such as ArcCHECK (Sun Nuclear Corp., Melbourne, FL), are quite useful for dosimetry measurements.…”
Section: Discussionmentioning
confidence: 99%